PERKEMBANGAN AKADEMIK ANAK BERKEBUTUHAN KHUSUS DI LINGKUNGAN FORMAL - Nurbaiti (STKIP Subang, 2026)
This study aims to describe the academic development of children with special needs who have a combination of hyperactivity and slow learning characteristics, analyze the supporting and inhibiting factors influencing their academic progress, and evaluate the strategies applied by teachers to support their academic development in formal education settings. The research was conducted at SD Negeri 8 Biau, Buol Regency, Central Sulawesi, using a qualitative approach with a case study method. Data collection techniques included observation, semistructured interviews, and documentation. The results show that the academic development of children with special needs progresses gradually, especially in reading, writing, and arithmetic skills. Key supporting factors include the active role of teachers, parental support, and positive social interactions at school. Meanwhile, inhibiting factors involve limited understanding among regular teachers about special needs, the absence of special education assistants, and inadequate support at home due to parents’ limited education and economic resources. Teachers applied individual learning approaches, visual media, simplified language, repetition of material, and positive reinforcement to keep students focused and engaged in learning activities. The findings conclude that collaboration between teachers, parents, and the school environment plays a crucial role in supporting the academic development of children with special needs. With appropriate strategies and a supportive environment, children with hyperactive and slow learner conditions still have the potential to grow and achieve academically in formal educational settings.